MOLECULAR IDENTIFICATION OF Pepper yellow leaf curl Indonesia virus ON CHILI PEPPER IN NUSA PENIDA ISLAND - Selangga, Dewa Gede Wiryangga; Listihani, Listihani (Universitas Lampung, 2021)
Molecular identification of Pepper yellow leaf curl Indonesia virus on chili pepper in Nusa Penida Island. Pepper yellow leaf curl Indonesia virus (PYLCV) has been reported as caused yellow leaf curl disease in Bali Island since early 2012. Dominant symptoms of PYLCV infection in chili pepper were yellowing, leaf curl, yellow mosaic, and mottle. Bemisia tabaci, has been known to vector on the case yellow leaf curl disease. Observations on the Nusa Penida Island in 2020 showed symptoms such as yellow leaf curl disease, however, identification of PYLCV in Nusa Penida Island has not been studied. Molecular identification was conducted using polymerase chain reaction and sequence analysis. Data collected in this study was disease symptoms and disease incidence. The results showed that dominant disease symptoms caused by virus from Nusa Penida were yellow mosaic, yellowing, and mottle. Universal DNA fragments of 912 bp were successfully amplified from 50 leaf samples using Begomovirus degenerate primers SPG 1 (5’-CCCCKGTGCGWRAATCCAT-3’) and SPG 2 (5’ATCCVAA YWTYCAGGGAGCT-3’). Sequence analysis showed that the isolate from Nusa Penida was a Pepper yellow leaf curl Indonesia virus with a 98–100% homology with several reference isolates.